2009
DOI: 10.1136/vr.164.12.373
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis by PCR of Coxiella burnetii in aborted fetuses of domestic ruminants in Portugal

Abstract: Coxiella burnetii is a non-motile, obligate intracellular, Gram-negative microorganism that is the causative agent of Q fever, a widespread zoonosis. Cattle, sheep and goats are considered to be the primary sources of human infection (McQuiston and Childs 2002), although occasional zoonotic infections have been linked to pets, birds, ticks and other arthropods (Buhariwalla and others 1996, Maurin and Raoult 1999). Human beings are infected by the inhalation of contaminated aerosols or the ingestion of infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 13 publications
1
8
1
Order By: Relevance
“…Recent PCR-based studies identified C. burnetii in 9% of tested sheep flocks in northern Spain [21] and in 18.6% of farms with small ruminants in southern Italy [22]. Two further studies on samples obtained from either ovine abortions in Sardinia [23] or ovine foetal organ samples and placentae in Portugal [24] discovered C. burnetii in 10.9% and in 36% of the cases, respectively. A Turkish study assessing milk samples collected from 22 flocks determined 6.5% C. burnetii positive animals in 12 flocks with a history of abortion and no positives in flocks without a history of abortion [25].…”
Section: Discussionmentioning
confidence: 99%
“…Recent PCR-based studies identified C. burnetii in 9% of tested sheep flocks in northern Spain [21] and in 18.6% of farms with small ruminants in southern Italy [22]. Two further studies on samples obtained from either ovine abortions in Sardinia [23] or ovine foetal organ samples and placentae in Portugal [24] discovered C. burnetii in 10.9% and in 36% of the cases, respectively. A Turkish study assessing milk samples collected from 22 flocks determined 6.5% C. burnetii positive animals in 12 flocks with a history of abortion and no positives in flocks without a history of abortion [25].…”
Section: Discussionmentioning
confidence: 99%
“…PCR analysis of multiple tissues from aborted lambs with PCR positive placenta, but without a histopathologically confirmed cause of abortion, have revealed C. burnetii DNA in multiple tissues. [27,30,31,35,64,74-80]. These findings indicate that C. burnetii may infect the fetus itself by the aminotic-oral route and haematogenously (Figure 1).…”
Section: Introductionmentioning
confidence: 93%
“…Parisi et al [24] and Clemente et al [27] found 17.2% and 11.6% PCR positive animals among cattle that had aborted, respectively. Real time PCR has been claimed to be a reliable tool in diagnosing Q fever abortion.…”
Section: Introductionmentioning
confidence: 99%
“…4,28,29 Studies of cattle have also shown a high seroprevalence of C burnetii infection suggesting that Q fever is far from being a negligible disease in Portugal. 30,31 Despite several clinical cases of Q fever reported in the Portuguese literature, [32][33][34] only two studies have investigated the clinical and epidemiological situation of the disease in the country. 27,35 Q fever is a notifiable disease in Portugal since January 1, 1999 and an average of 0.1 cases per 10 5 inhabitants per year have been reported.…”
Section: Introductionmentioning
confidence: 99%